Analisis Rasio Aktivitas Terhadap Profitabilitas Pada Perusahaan Sub Sektor Barang Dan Konsumsi - Ridho Deza Perkasa; Likanopa Syentia (GLOBAL SCIENTS PUBLISHER, 2025)
The purpose of this study is to analyze the influences of cash turnover, accounts receivable turnover, and inventory turnover on profitability. The population in this study are all of companies in consumer goods industry sector. The final sample in this study ware 35 consumer goods industrial companies which obtained by using purposive sampling method. The data used in this research is secondary data. The analytical model used to solve the problem in this study is multiple linear regression with a significant level of 5%. Based on the results of the analysis, showed that cash turnover, receivables turnover, and inventory turnover have positive effect on the profitability of the consumer goods industry sub-sector companies listed on the Indonesia Stock Exchange during 2018-2022.